2020
DOI: 10.1371/journal.pone.0237777
|View full text |Cite
|
Sign up to set email alerts
|

KICK OUT PD: Feasibility and quality of life in the pilot karate intervention to change kinematic outcomes in Parkinson’s Disease

Abstract: Background Multiple exercise modalities and mindfulness activities are beneficial in Parkinson's Disease (PD). Karate is a martial art that combines aerobic and large-amplitude movements, balance and core training, and mindfulness, suggesting a potential benefit for individuals with PD from multiple perspectives. Objective To evaluate the feasibility of community-based Shotokan karate classes involving physical activity and mindfulness among individuals with mild-to moderate-stage PD, and to explore the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…Following the training intervention, all participants showed improved performance in postural control through a decrease in time taken for dynamic postural reaction during the balance test. This enhanced dynamic balance performance leads to better postural control in older adults with or without chronic conditions, which is congruent with similar studies that observed the stabilizing effects of 'hard' martial arts [3,13,16,17,40]. Balance requires complex neuromechanical integration of muscular, somatosensory, visual, and vestibular coordination [2,17,[41][42][43].…”
Section: Dynamic Balance and Postural Corrections Improved By Karate Trainingsupporting
confidence: 84%
See 4 more Smart Citations
“…Following the training intervention, all participants showed improved performance in postural control through a decrease in time taken for dynamic postural reaction during the balance test. This enhanced dynamic balance performance leads to better postural control in older adults with or without chronic conditions, which is congruent with similar studies that observed the stabilizing effects of 'hard' martial arts [3,13,16,17,40]. Balance requires complex neuromechanical integration of muscular, somatosensory, visual, and vestibular coordination [2,17,[41][42][43].…”
Section: Dynamic Balance and Postural Corrections Improved By Karate Trainingsupporting
confidence: 84%
“…Effect size (Cohen's d) was calculated to provide a standardized magnitude of changes [39]. Small (0.2-0.5), medium (> 0.5-0.8), and large (> 0.8) effect sizes descriptors were used as in a similar study [13]. The level of signi cance was set at p < 0.05, with group data reported to 3 decimal places and p < 0.05 for the single subject and the group 95% CI analyses.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
See 3 more Smart Citations